Romanesque and the past
1 online resource
Keywords: The nineteen papers collected in this volume explore a notable phenomenon, that of retrospection in the art and architecture of Romanesque Europe. They arise from a conference organized by the British Archaeological Association in 2010, and reflect its interest in how and why the past manifested itself in the visual culture of the 11th and 12th centuries. This took many forms, from the casual re-use of ancient material to a specific desire to re-present or emulate earlier objects and buildings. Central to it is a concern for the revival of Roman and early medieval forms, spolia, selective quotation, archaism and the construction of histories. The individual essays presented here cover a wide range of topics and media: the significance of consecration ceremonies in the creation of architectural memory, the rise of pictorial concepts in 12th-century chronicles, the creation of history in the Paris of Hugh of St-Victor, and the appeal of the works of Bernward of Hildesheim and of Hrabanus Maurus in the centuries after their deaths. There are studies of buildings and the ideological purpose behind them at Tarragona, Ripoll, Cluny, Pannonhalma (Hungary), La Roccelletta (Calabria), and Old St Peter's, comparative studies of Trier, Villenauxe and Glastonbury, and of Bury St Edmunds, Rievaulx and Canterbury, and wide-ranging papers on the tantalizing evidence for an engagement with an overseas past in Ireland, an Anglo-Saxon past in England, and a Milanese past among the aisleless cruciform churches of Augustinian Europe. The volume concludes with an assessment of the very concept of Romanesque.